FOUNDATION IN SCIENCE STUDIES - BIOLOGICAL FIELD TRIP REPORT: Brief Documentation on Selected Timber-Related Plants Species with Commercial Value in Kubah National Park, Sarawak - Mohd Ridwan, Abd Rahman; Mohamad Fhaizal, Mohamad Bukhori; Muhamad Ikhwan, Idris; Mohamad Razif, Othman; Mohd Aminudin, Mustapha; Noorazman, Samsudin (UNIMAS Publisher, 2019)
In order to accommodate, enhance and accomplish the course learning objectives of ecology, biodiversity and environment in the class, in situ erudition remain the finest key to complement by conducting actual fieldwork experiments. The specific objectives of the fieldwork are to ensure sustainable learning, adopting best practice in scientific documentation, and implementing holistic and integrated learning approach in the course. Therefore, related case study was given to the students and resulted with a few attributes. Seven different family with 12 different species of timber-related plants were identified and classified throughout the study. To date, timber-related plants species is known to provide several benefits and usage to human as well as other organisms. The information present is useful for research and education purposes, developing a conservation awareness, plan and management, and also helps in promoting ecotourism. The trip was conducted to introduce a comprehensive learning experience to the students in biodiversity-related discipline